Microeconomic effects of competition on productivity in the EU - Vahter, Priit (2010)
Differences in the toughness of competition are likely to be one of the major determinants of the large dispersion in productivity, costs and output prices across firms even within narrowly defined sectors and geographical markets. This dissertation examines how increase in the intensity of international competition affects productivity and other performance measures: at the firm, industry, and geographical market levels. The dissertation combines three empirical studies of three distinct types of changes in the competition environment.